SYNTHESIS, CHARACTERIZATION, AND APPLICATION OF MGO FROM BITTERN: A RIVIEW 2018 - 2025 - Devilia Yuanita Nuni Widiarti; Nuni Widiarti (Prodi Kimia, 2026)
Bittern, a liquid by-product of the salt industry, has emerged as a promising and sustainable alternative raw material for the synthesis of Magnesium Oxide (MgO). This literature review comprehensively examines recent developments within the 2018-2025 period concerning the synthesis, characterization, and diverse applications of MgO derived from bittern. Emphasis is placed on the potential of bittern as an economical magnesium source and its utilization aligning with circular economy principles. Predominant synthesis methods, such as chemical precipitation (using NaOH or Ca(OH)₂) and electrolysis, are discussed in depth, highlighting key process parameters and their influence on final product properties. Characterization results of bittern-derived MgO, including crystal structure and phase analysis using X-ray Diffraction (XRD), surface morphology analysis via Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM), and specific surface area determination by the Brunauer-Emmett-Teller (BET) method, are summarized from various studies. This review also explores the various applications of MgO synthesized from bittern, including as an adsorbent for pollutant removal (dyes and heavy metal ions), a catalyst and photocatalyst in chemical reactions, an antibacterial agent against pathogenic microorganisms, a refractory material for high-temperature applications, and in agriculture as a magnesium nutrient source. The positive environmental implications of utilizing waste bittern to produce this value-added material are also emphasized. The conclusion of this review affirms the significance of research in valorizing bittern into MgO and identifies prospects and challenges for future development, including process optimization, upscaling, and exploration of innovative applications.